Pengaruh Edukasi Buku Saku Terhadap Pengetahuan Ibu Rumah Tangga Tentang Demam Berdarah Dengue Di Puskesmas Gang Sehat - Abdullah, Muhammad Riski; Hidayah, Nurul; Nisma (STIKes YARSI Pontianak, 2025)
Background: Dengue fever (DHF) is an endemic disease that creates a high mortality rate and is often considered an extraordinary event. In 2023, Indonesia recorded more than 143,000 cases of DHF and ranked the highest in Southeast Asia. One of the main causes of the high number of DHF cases is the low knowledge of the community regarding its prevention and management. This study aimed to determine the effect of education through a pocket book on housewives' knowledge about DHF. Methods: The study used a quasi-experimental one group pretest-posttest design with 17 housewives selected through total sampling. Results: The pretest results showed that most respondents had poor knowledge of dengue (82.4%), while 17.6% had moderate knowledge. After education through the pocket book, the posttest results showed an improvement, with 88.2% of respondents reaching a good level of knowledge and 11.8% in the moderate category. This finding proves that the pocket book is effective in improving respondents' knowledge about DHF. Statistical analysis using the Wilcoxon test showed a p value <0.05, indicating a positive effect of education through the pocket book. Conclusion: The conclusion of this study shows that the pocket book as an educational media is effective in increasing housewives' knowledge about DHF. It is recommended that the pocket book be used more widely in public health education programs to reduce the incidence of DHF.